The Identification of Phytocompounds from Limonia acidissima L. Fruit: A Short Report and Updated Review – Focusing on Antihyperuricemic and Antiarthritic Activities - Yusnaini, Rika; Ikhsan; Iskandar; Junaidi; Salamah; Adam; Erithrina (PT Inovasi Pratama Internasional, 2023)
The side effects of using anti-gout and anti-inflammatory drugs in patients with hyperuricemia and gouty arthritis are the reason to get alternative, safer herbal medicines. To answer the call from the Indonesian government to explore the natural product potential as treatment modalities against various diseases, we performed an investigation on Limonia acidissima L. fruit. Extraction of the Limonia acidissima L. fruit was carried out by means of maceration using different solvents (n-hexane, ethyl acetate, ethanol, and methanol), performed sequentially. Phytoconstituents of each extract were further determined by using Gas Chromatography – Mass Spectroscopy (GC-MS). The results revealed that L. acidissima fruit is rich with fatty acids including oleic acid, n-hexadecanoic acid, palmitoleic acid, and octadecanoic acid. Several important plant sterols, such as sitosterol, stigmasterol, ergost-5-en-3-ol, (3beta.), were also found in the extract. Updated literature review confirmed the potential of Limonia acidissima L. fruit application as phytomedicine. To conclude, we recommend further investigation on the L. acidissima fruit potentials as antihyperuricemic and antiarthritic therapies